Wilfrid H.G. Haacke and Eliphas Eiseb. Khoekhoegowab-English / English-Khoekhoegowab Glossary / Mfdi Saogub - Snyman, J.W. (Lexikos, 2000)
The publication of the two-way Khoekhoegowab-English / English-Khoekhoegowab Glossary by Prof. Wilfrid H.G. Haacke and Pastor Eliphas Eiseb is a most welorne contribution to the lexicographical literature of Namibia. This glossary, hich is an extract from the more extensive Khoekhoegowab Dictionary (forthcoming) by the same authors, contains more than 4 300 Khoekhoegowab entries. Apart from reviewing the glossary, the following comments also comply with Prof. Haacke’s request (p. v) to supply him with "anything useful for a future edition". The glossary has as its predecessors J. Olpp’s Nama-Deutches Worterbuch (Eberfeld, 1888), J.C. Kronlein’s Wortschatz der Khoi-khoin (Berlin, 1889) and F. Rust’s Deutsch-Nama Worterbuch (Windhoek, 1960). Although the glossary is not solely intended for educational purposes, it is bound to have a significant impact on the teaching and development of Khoekhoegowab in Namibia.